Implementasi Rias Fantasi dengan teknik Body Painting pada Patung Berbahan Clay Bersumber Ide Badak Jawa - Ashila Tiara Hanum; Trisnani Widowati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Javan rhinoceros (Rhinoceros sondaicus) is an endemic Indonesian animal that is critically endangered and has distinctive visual characteristics, such as a sturdy body, thick, folded skin, and dark gray color. These visual characteristics have the potential to be a source of inspiration in creating fantasy makeup through body painting techniques. This study aims to develop fantasy makeup on clay sculptures inspired by the Javan rhinoceros, as well as to assess the validity of the instrument and the feasibility of the resulting work. This study uses a research and development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through instrument validation sheets by experts and work feasibility assessment sheets, then analyzed using Aiken's V and descriptive percentages. The results showed that the assessment instrument had an Aiken's V value of 0.81 with a very valid category, while the developed work obtained an average feasibility of 90.97% with a very feasible category. These results indicate that the application of body painting techniques to clay sculptures is able to produce fantasy makeup works that meet the aesthetic, visual, creativity aspects, and suitability with the character of the object of inspiration. The implications of this research indicate that visuals of Indonesia's endemic fauna can be utilized as a source of creative ideas in developing works and teaching beauty art.